The online effect of clash is durational lengthening, not prominence shift: Evidence from Italian. (March 2022) - Burroni, Francesco; Tilsen, Sam
Highlights: Two production studies of clash with 24 native speakers of Italian in total. Correlates of clash are duration and formant changes in the final vowel of word one. Findings interpreted as changes to prosodic boundaries and/or gestural dynamics. Two dynamical models of the observed changes in clash are presented. Reported changes to prominence best interpreted as biased lexical selection. Abstract: A fundamental question about speech is whether it is governed by rhythmic constraints. One phenomenon that may support the existence of such constraints is the rhythm rule, a phonological pattern hypothesized to resolve prominence clashes and enforce alternations of prominent and non-prominent syllables via shift/deletion of stress and/or pitch accents. We evaluated evidence for the rhythm rule by studying the acoustic correlates of clash in two experiments with speakers of Italian. We found that the first prominent syllable in a clash displays a durational increase and more extreme formant values, when compared to no clash. Thus, a clash is manifested as a localized decrease in speech rate, not as a change to the prominence profile of a word. Since durational increases have been reported for other languages, we argue that they are an online acoustic correlate of clash. We compare two dynamical models of the durational effects, rooted in the framework of Articulatory Phonology: a π-gesture model and a feedback modulation model. Based on our findings, we argue that the rhythm rule is best conceptualized as the result of contextual biases on lexical selection of prominence patterns.